Breaking paracyclophane: the unexpected formation of non-symmetric disubstituted nitro[2.2]metaparacyclophanes - Patel, Suraj; Dais, Tyson N.; Plieger, Paul G.; Rowlands, Gareth J. (Beilstein Journal of Organic Chemistry, 2021)
Substituted [2.2]metaparacyclophanes are amongst the least studied of the simple cyclophanes. This is undoubtedly the result of the lengthy syntheses of these compounds. We report the simple synthesis of a rare example of a non-symmetric [2.2]metaparacyclophane. Treatment of [2.2]paracyclophane under standard nitration conditions gives a mixture of 4-nitro[2.2]paracyclophane, 4-hydroxy-5-nitro[2.2]metaparacyclophane and a cyclohexadienone cyclophane.
Keywords: cyclophane; metaparacyclophane; nitration; paracyclophane; rearrangement